2019
DOI: 10.1007/s12033-019-00201-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Expression Vectors Based on the pIGDM1 Plasmid

Abstract: Escherichia coli is one of the most widely used hosts for the production of heterologous proteins. Within this host, the choice of cloning vector constitutes a key factor for a satisfactory amplified expression of a target gene. We aimed to develop novel, unpatented expression vectors that enable the stable maintenance and efficient overproduction of proteins in E. coli. A series of expression vectors based on the ColE1-like pIGDM1 plasmid were constructed. The vectors named pIGDMCT7RS, pIG-DM4RS and pIGDMKAN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…For some proteins, the differences in the vectors also affect the soluble expression of the protein. [ 28 ] Expression vectors pET‐28a and pGEX‐4T‐1 were employed to express Pul13552 in this study. The nucleic acid gel electrophoresis was employed to verify the gene of pul13552 ( Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For some proteins, the differences in the vectors also affect the soluble expression of the protein. [ 28 ] Expression vectors pET‐28a and pGEX‐4T‐1 were employed to express Pul13552 in this study. The nucleic acid gel electrophoresis was employed to verify the gene of pul13552 ( Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] Besides, enzyme activity was greatly inhibited by α‐cyclodextrin (0.1%) and urea (2 M), but activated by ethylene diamine tetraacetic acid (EDTA) (5 mM) and dithiothreitol (DTT) (2 mM). For the activation by the EDTA, it has been reported that when the concentration of Ca 2+ and Mg 2+ increases, the activity of the Pul GT decreases, [ 28 ] wherefore, the existence of the EDTA could reduce the concentration of the metal ions to increase the activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Constitutively active promoters have been successfully, albeit infrequently, employed in E. coli for producing recombinant proteins [58][59][60][61][62][63] . We demonstrated that two constitutive promoters allowed constant production of sfGFP at low levels (i.e., no obvious green fluorescence in cultures by visual observation, in contrast to sfGFP under T7 promoter).…”
Section: Discussionmentioning
confidence: 99%